Dispersal of Aedes aegypti L. and Aedes albopictus skuse (Diptera: Culicidae) in a university campus in Selangor, Malaysia - Wan-Norafikah O.,; Khairul-Hazim K.,; Nurul-Najiyah M.,; Siti-Nurdiyana M.,; Nur-Syaahidah K.,; Atiqah-Nazirah R., (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2020)
This study was carried out to determine the dispersal of Aedes aegypti and Ae. albopictus in a university campus located in Selangor, Malaysia. An ovitrap surveillance was conducted for both horizontal and vertical dispersal study, respectively. Results showed that Ae. albopictus population was more abundant than Ae. aegypti population in the entire environment of the campus. However, mixed breeding of both species of Aedes larvae was also detected within 23.53% of ovitraps recovered. Meanwhile, the results of vertical dispersal study showed that Ae. aegypti was the predominant indoor breeder in Residential College 2 (RC 2). Hence, mosquito control activities within the university campus should be continuously conducted and monitored to prevent the transmission of any Aedes-borne diseases among the university staff, students and visitors.